Mango Growers’ Compliance with Public Good Agricultural Practices Standard: A Comparative Study in Northern Thailand - Amekawa, Yuichiro; Tiyayon, Chantalak; Treewannakul, Panamas; Sawarng, Nootchakarn (Asian Journal of Agriculture and Rural Development, 2022)
This study investigated the effectiveness of Thailand’s public good agricultural practices certification initiative (Q-GAP) in improving export-oriented mango farmers’ awareness and practices relating to food safety and quality assurance. Two groups of certified farmers in Northern Thailand (one from Chiang Mai Province and the other from Phitsanulok Province), comprising a total of 96 samples, were surveyed for comparative analysis. Many items of the comparison showed no significant differences between the two groups of farmers (specifically, the use of synthetic pesticides and non-synthetic pest control methods, record-keeping, and agrochemical safety and handling practices). One significant difference worth mentioning was related to the farmers’ ability to link the goal of the Q-GAP policy to food safety assurance; when compared to Phitsanulok, approximately 35% more farmers in Chiang Mai demonstrated such an understanding. This contradicted the more experience and days of training on Q-GAP the farmers in Phitsanulok had in comparison to those in Chiang Mai. Moreover, the rates of understanding in both areas were significantly lower than those identified in previous Q-GAP studies of less export-oriented crops. The export-oriented mango farmers might be trained to regard Q-GAP certification as a type of license to export their mango produce, rather than as a tool to improve their food safety and quality assurance.